Systematic epidemiological and clinical comparisons across all 12 DSM-IV psychotic diagnoses in the Cavan–Monaghan First Episode Psychosis Study (CAMFEPS). Issue 4 (20th March 2021) - Nkire, Nnamdi; Scully, Paul J.; Browne, David J.; Baldwin, Patrizia A.; Kingston, Tara; Owoeye, Olabisi; Kinsella, Anthony; O'Callaghan, Eadbhard; Russell, Vincent; Waddington, John L.
Abstract: Background: Research on psychotic illness is loosening emphasis on diagnostic stringency in favour of including a more dimensionally based conceptualization of psychopathology and pathobiology. However, to clarify these notions requires investigation of the full scope of psychotic diagnoses. Methods: The Cavan–Monaghan First Episode Psychosis Study ascertained cases of first episode psychosis across all 12 DSM-IV psychotic diagnoses via all routes to care: public, private or forensic; home-based, outpatient or inpatient. There was no arbitrary upper age cut-off and minimal impact of factors associated with variations in social milieu, ethnicity or urbanicity. Cases were evaluated epidemiologically and assessed for psychopathology, neuropsychology, neurology, antecedent factors, insight and quality of life. Results: Among 432 cases, the annual incidence of any DSM-IV psychotic diagnosis was 34.1/100 000 of population and encompassed functional psychotic diagnoses, substance-induced psychopathology and psychopathology due to general medical conditions, through to psychotic illness that defied contemporary diagnostic algorithms. These 12 DSM-IV diagnostic categories, including psychotic disorder not otherwise specified, showed clinical profiles that were consistently more similar than distinct. Conclusions: There are considerable similarities and overlaps across a broad range of diagnostic categories in the absence of robust discontinuities between them. Thus, psychotic illness may be of such continuity that it cannot be fully captured by operational diagnostic algorithms that, at least in part, assume discontinuities. This may reflect the impact of diverse factors each of which acts on one or more overlapping components of a common, dysfunctional neuronal network implicated in the pathobiology of psychotic illness.